2018
DOI: 10.22175/mmb2017.07.0038
|View full text |Cite
|
Sign up to set email alerts
|

Ractopamine Hydrochloride Did Not Impact Carcass Traits, Muscle Fiber Types, or Sensory Traits of Long-Fed Yearling Heifers

Abstract: Crossbred heifers (n = 64; animal was the experimental unit) were assigned to 1 of 8 treatments in a 4 × 2 factorial arrangement, with 4 treatment days-on-feed (DOF; 79, 100, 121, 142) and 2 levels of ractopamine hydrochloride (RAC) supplementation (0 or 300 mg × hd–1 × d–1). At 24 h postmortem, carcass traits were determined by trained personnel and longissimus samples were removed for muscle fiber type analyses. Boneless strip loins (IMPS #180) were fabricated and vacuum-packaged at 24 h postmortem and aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…For some meat consumers, one of the most important factors affecting the purchasing decision is the amount of intramuscular fat [ 35 ]. In our study, FA supplementation decreased subcutaneous fat deposition without affecting marbling scores, obtaining a better score than others reported by ractopamine [ 29 , 36 ]. Similarly, the meta-analysis carried out by Andretta et al [ 5 ] indicated that ractopamine significantly reduces backfat thickness, but without affecting intramuscular fat content.…”
Section: Discussionsupporting
confidence: 50%
“…For some meat consumers, one of the most important factors affecting the purchasing decision is the amount of intramuscular fat [ 35 ]. In our study, FA supplementation decreased subcutaneous fat deposition without affecting marbling scores, obtaining a better score than others reported by ractopamine [ 29 , 36 ]. Similarly, the meta-analysis carried out by Andretta et al [ 5 ] indicated that ractopamine significantly reduces backfat thickness, but without affecting intramuscular fat content.…”
Section: Discussionsupporting
confidence: 50%
“…Supplementation with RH did not improve the HCW or LM area of the BA treatment compared to IMP but resulted in advanced carcass maturity. Others have reported no difference in HCW ( Quinn et al, 2008 ; Strydom et al, 2009 ; Hales et al, 2016 ; Hunter-Beasley, et al, 2018 ; Trotta et al, 2019 ) or LM area ( Walker et al, 2006 ; Quinn et al, 2008 ; Strydom et al, 2009 ; Hales et al, 2016 ; Hunter-Beasley, et al, 2018 ) of RH supplemented cattle compared with non-supplemented controls. However, it is unclear why the LM area of BA was 4.6 cm 2 smaller than IMP in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Limited information exists regarding the influence of monensin and tylosin on KPH, however, the increase in KPH of steers in the ANT treatment compared to NT may be due to increased days on feed, not a direct result of these supplements. Increasing days on feed has been shown to increase KPH ( Hunter-Beasley et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%